The articulated distance ladder. (November 2017) - Mould, Jeremy
How do you build a (distance) ladder from the closest stars to the far-away supernovae and all the way back to the last scattering surface of the Universe?Jeremy Mould summarizes some of the highlights of the Stellar Populations and the Distance Scale conference.